2023
DOI: 10.3390/tropicalmed8010047
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis Calreticulin Interferes with C1q-Mediated Complement Activation

Abstract: As a zoonotic disease caused by Echinococcus multilocularis larvae, alveolar echinococcosis (AE) is one of the most severe forms of parasitic infection. Over a long evolutional process E. multilocularis has developed complex strategies to escape host immune attack and survive within a host. However, the mechanisms underlying immune evasion remain unclear. Here we investigated the binding activity of E. multilocularis calreticulin (EmCRT), a highly conserved Ca2+-binding protein, to human complement C1q and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has been shown that CRTs are highly conserved in several parasite species, from protozoa ( Trypanosoma , Amoeba , and Leishmania ) to helminths ( Echinococcus , Opisthorchis viverrini , Brugia malayi and Necator americanus ), and play important roles in the adaptation of parasites to the hostile environments and escape from host immune responses ( 4 , 7 , 21 , 45 , 46 ). Our previous studies have determined that TsCRT can bind to human complement C1q and inhibit C1q-initiated classical complement activation to enable the parasite to evade host first-line immune attack ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CRTs are highly conserved in several parasite species, from protozoa ( Trypanosoma , Amoeba , and Leishmania ) to helminths ( Echinococcus , Opisthorchis viverrini , Brugia malayi and Necator americanus ), and play important roles in the adaptation of parasites to the hostile environments and escape from host immune responses ( 4 , 7 , 21 , 45 , 46 ). Our previous studies have determined that TsCRT can bind to human complement C1q and inhibit C1q-initiated classical complement activation to enable the parasite to evade host first-line immune attack ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that E. multilocularis uses Em CRT to interfere with the host immune attack process, which may be a strategy of immune evasion. This study further indicates that Em CRT could be developed as a vaccine candidate against E. multilocularis infection [ 5 ]. The third study aimed to investigate the maternal-fetal immune transfer of Nipah virus [ 6 ].…”
mentioning
confidence: 81%